Pengaruh Community Building Dan Social Marketing Di Platform Steam Terhadap Engagement Pengguna Dan Pembelian Game (Studi Pada Pengguna STEAM Di Komunitas Grup) - Muhammad Hilmi Assydqi; Amelindha Vania (Indo Publishing, 2025)
This study aims to explore the impact of community building and social marketing on the Steam platform on user engagement levels and game purchase decisions. As one of the largest digital distribution platforms in the world, Steam utilises the user community as a key element in its marketing strategy. This study used a survey method with a quantitative approach, involving 300 respondents who are active Steam users. Data analysis was conducted using linear regression to evaluate the relationship between the variables under study. The research findings revealed that community building involving interaction between users through forums, discussion groups and other features can significantly increase user engagement. In addition, social marketing through promotion on social media and co-operation with influencers was also shown to positively influence game purchase decisions. The results of this study provide an understanding of the important role of community and social marketing strategies in increasing user loyalty and driving increased sales on digital platforms. This research is expected to serve as a reference for game developers and marketers in optimising community-based marketing strategies on digital distribution platforms.